2023
DOI: 10.1177/09731296231173558
|View full text |Cite
|
Sign up to set email alerts
|

Screening the Chemical Composition and Bioactivity of Cerasus serrulata Flower Extracts Using Two Extraction Methods

Abstract: Background Cerasus serrulata has an excellent antioxidative, antibacterial, and anti-alopecia effect, but its active ingredients and the underlying mechanism are currently unclear, in addition to the fact that the active products vary with the extraction methods. Aim Therefore, this study aims to clarify the active components and antioxidative property of C. serrulata extracted by two different methods (low-temperature vacuum extraction and ethanol extraction) and explore its potential biofunction. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The research conducted by Zhang et al (2023) on the anti-alopecia effects of Cerasus serrulata was carried out using two different extraction methods, namely cold vacuum extraction and ethanol extraction. The results of the study showed that the composition of compounds in the Cerasus serrulata extract varied depending on the extraction method used.…”
Section: Cerasus Serrulatamentioning
confidence: 99%
See 2 more Smart Citations
“…The research conducted by Zhang et al (2023) on the anti-alopecia effects of Cerasus serrulata was carried out using two different extraction methods, namely cold vacuum extraction and ethanol extraction. The results of the study showed that the composition of compounds in the Cerasus serrulata extract varied depending on the extraction method used.…”
Section: Cerasus Serrulatamentioning
confidence: 99%
“…Additionally, the extract also exhibited strong antioxidant activity in scavenging free radicals and demonstrated good antibacterial abilities in inhibiting the growth of five common bacterial strains. Studies on the alopecia rat model showed that the use of Cerasus serrulata extract had a positive effect on maintaining hair follicles, regulating the expression of VEGF, IL-6, β-catenin, FGFR, and IGF-1 proteins, and reducing DHT and 5α-reductase levels (Zhang et al, 2023).…”
Section: Cerasus Serrulatamentioning
confidence: 99%
See 1 more Smart Citation